Estimation of loads on a horizontal axis wind turbine operating in yawed flow conditions. (25th August 2014) - del Campo, V.; Ragni, D.; Micallef, D.; Diez, F. J.; Ferreira, C. J. Simão
Abstract Stereoscopic particle image velocimetry (SPIV) has been used to characterize the flow around the blade of a yawed horizontal axis wind turbine model. The goal was to assess the possibility of obtaining the 3D velocity field around the blade, the pressure distribution, and the aerodynamic loads being exerted on the blade under unsteady flow conditions. The SPIV equipment was mounted on a traverse system and provided with phase‐locked velocity planes perpendicular to the blade axis, scanning the blade from the root to the tip, at three different azimuthal positions, so as to have information of the time variation of the flow. The pressure distribution and the aerodynamic loads on each plane were obtained via 3D formulation. Main differences encountered when measuring loads in yawed flow compared with axial flow have been discussed. Finally, the consistency of the results with similar results obtained computationally with a panel model was assessed. The proposed methodology presents one step further in the application of SPIV to measure forces on a horizontal axis wind turbine, assessing the possibility of estimating the blade loads when the turbine is operating under non‐axial flow conditions, with the goal of better simulating real working operating regimes in a wind farm, where the flow is typically not uniform. The proposed methodology could be developed and used to better understand relevant wind energy issues such as dynamic loading and active load control efficiency, in the future. The processed and averaged flow fields from the experimental SPIV data are made available online to the reader. See appendix for description of the files. Copyright © 2014 John Wiley & Sons, Ltd.